Theology and the globalized present : feasting in the future of God - McDowell, John C. (Dispatches (Minneapolis, Minn.), 2019)
Theology and the Globalized Present focuses on the world's future in God and God's creativeness. In response to a globalized economy that reconfigures time to the detriment of human flourishing, McDowell presents a re-imagined theological vision of eschatological memory and Eucharistic performance. This entails not so much a dreaming of a different world as a dreaming of this world differently. The theological materials offer a temporality that is hope-generating, critically attentive to the inequitable character of features of our world, and educative of ethical wisdom in a self-regulating and emancipatory witness of remembering and anticipating the transformative presence of God.